اغتراب الذات وتشظي الهوية: قراءة نقدية في كتاب "قهوة باليورانيوم" لأحمد خالد توفيق - الماشطة، همام ياسين شكر (جامعة بابل - مركز بابل للدراسات الحضارية والتاريخية, 2023)
تعيش الذات في ظل الخطابات الإيديولوجية والعولمية المستفحلة أزمةً وغربةً ثقافيةً وفكريةً، تعظم هذه الأزمة كلما اتسعت الهوة بين ما تؤمن به الذات من الأفكار والعادات والقيم، وبين ما لا تؤمن به وتنبذه. ففي كل مجتمع ثمة معتقدات وعادات قيمية ثابتة، يشكل تجاوزها انتهاكاً صارخاً لثقافة ذلك المجتمع، فتجاوزها وتذويبها ومن ثم استبدالها بأخرى وافدة وجديدة مما يسلب الذات هويتها الثقافية والاجتماعية والدينية، ويلقي بها في الاغتراب والعزلة. تلقي هذه الدراسة الضوء على تمثلات الاغتراب وتشظي الهوية في كتاب (قهوة باليورانيوم) للدكتور أحمد خالد توفيق، ففي الكتاب مقالات أدبية، رصدت بأسلوب ساخر، أهم العادات والتقاليد التي عمقت من أزمة الذات واغترابها في المجتمع المصري، وأعادت في الوقت نفسه هيكلة الهوية وتنميطها بنمط لا يتوافق مع عادات وقيم المجتمع، الأمر الذي أفرز أصواتها ناقمة وناقدة للواقع المعولم إن صح التعبير وتكشف الدراسة أيضاً عن التقنيات التي وظفها الكاتب للتعبير فنياً عن ظاهرة الاغتراب سواء في العنوان أو المتن. The self lives in the shadow of extensive ideological and global discourses, a crisis, and cultural and intellectual alienation. This crisis is magnified whenever the gap widens between what the Self believes in terms of ideas, customs, and values and what it does not believe in and rejects. In every society, there are fixed beliefs and value habits; exceeding them constitutes a flagrant violation of the culture of that society; bypassing them, dissolving them, and then replacing them with new ones robs the self of its culture, social, and religious identity and throws it into alienation and isolation. This study sheds light on the representations of alienation and fragmentation of identity in the book Coffee with Uranium) by Dr. Ahmed Khaled Tawfik. In the book, literary essays observe in a satirical style the most important Customs and traditions that deepened the crisis of self and its alienation in Egyptian society and at the same time restructured identity and stereotyped it with a pattern that does not correspond to the Customs and values of society, which resulted in its voices criticizing and criticizing the globalized reality, so to speak The study also reveals the details that the writer employed artistically about the phenomenon of alienation, whether in the title or the text..
Keywords: الهوية الثقافية -- الأدب المعاصر -- الخطابات الأيديولوجية -- توفيق، أحمد خالد، ت. 2018 م